Lactate kinetics during passive and partially active recovery in endurance and sprint athletes - Taoutaou, Z.; Granier, P.; Mercier, B.; Mercier, J.; Ahmaidi, S.; Prefaut, C. (European Journal of Applied Physiology, 1996)
We investigated the effects of passive and partially active recovery on lactate removal after exhausting cycle ergometer exercise in endurance and sprint athletes. A group of 14 men, 7 endurance-trained (ET) and 7 sprint-trained (ST), performed two maximal incremental exercise tests followed by either passive recovery (20 min seated on cycle ergometer followed by 40 min more of seated rest) or partially active recovery [20 min of pedalling at 40% maximal oxygen uptake (VO2max) followed by 40 min of seated rest]. Venous blood samples were drawn at 5 min and 1 min prior to exercise, at the end of exercise, and during recovery at 1, 2, 3, 4, 5, 6, 8, 10, 15, 20, 30, 40, 50, 60 min post-exercise. The time course of changes in lactate concentration during the recovery phases were fitted by a bi-exponential time function to assess the velocity constant of the slowly decreasing component (tau 2) expressing the rate of blood lactate removal. The results showed that at the end of maximal exercise and during the 1st min of recovery, ET showed higher blood lactate concentrations than ST. Furthermore, ET reached significantly higher maximal exercise intensities [5.1 (SEM 0.5) W.kg-1 vs 4.0 (SEM 0.3) W.kg-1, P < 0.05] and VO2max [68.4 (SEM 1.1) ml.kg-1.min-1 vs 55.5 (SEM 5.1) ml.kg-1.min-1, P < 0.01]. There was no significant difference between the two groups during passive recovery for tau 2. During partially active recovery, tau 2 was higher than during passive recovery for both groups (P < 0.001), but ET recovered faster and sooner than ST (P < 0.05). Compared to passive recovery, the tau 2 measured during partially active recovery was increased threefold in ET and only 1.5-fold in ST. We concluded that partially active recovery potentiates the enhanced ability to remove blood lactate induced by endurance training.